Acid clearance and oesophageal sensitivity in patients with progressive systemic sclerosis. Issue 11 (November 1993) - Basilisco, G; Barbera, R; Molgora, M; Vanoli, M; Bianchi, P
Abstract : This study examined the hypothesis that impaired oesophageal peristalsis was associated with delayed oesophageal clearance of acid in patients with progressive systemic sclerosis (PSS), some of whom are thought to have impaired oesophageal sensitivity to acid. Sixteen patients with PSS had: (a) oesophageal manometry and endoscopy; (b) acid perfusion of the oesophagus with simultaneous measurement of intraoesophageal pH during perfusion and for the next 10 minutes; (c) 22 hour monitoring of intraoesophageal pH; and (d) an evaluation of reflux symptoms during and after perfusion and during overnight pH monitoring. By oesophageal manometry, eight patients had normal peristalsis and eight patients had impaired peristalsis. Oesophageal endoscopy was unremarkable in patients with normal peristalsis, whereas all patients with impaired peristalsis had oesophagitis. The time needed to clear the oesophagus of perfused acid was shorter (p < 0.01) in patients with normal peristalsis and acid clearance time was significantly correlated (p < 0.01) with acid exposure time during overnight pH monitoring. During and after oesophageal perfusion, the nature, duration, and severity of symptoms did not differ between the groups, but overnight symptoms lasted longer (p < 0.05) in patients with impaired peristalsis. It is concluded that in PSS: (1) Impaired oesophageal motility delayed the clearance of acid and increased the exposure time to acid. (2) Acid clearance time is a useful parameter of impaired oesophageal motor function. The assessment of acid clearance time can be used as an alternative to overnight pH monitoring, to assess the impairment of oesophageal acid clearance. (3) Oesophageal sensitivity to acid was preserved in patients with impaired peristalsis and oesophagitis. (4) Reflux symptoms lasted longer in patients with prolonged oesophageal acid exposure but were still reported for a small fraction of the total acid exposure time. Thus, reflux symptoms reflect poorly prolonged exposure of the oesophagus to acid and are not a reliable guide to acid injury of the oesophagus in PSS.